Guerrilla Diplomacy : the NLF's Foreign Relations and the Viet Nam War - Brigham, Robert K. (Cornell University Press, 2019)
In 1960 revolutionaries in South Viet Nam created the National Liberation Front, a political and military organization committed to overthrowing the Saigon government and liberating Viet Nam south of the seventeenth parallel. The role of the NLF during the war has been hotly debated, with officials in Washington claiming from the outset that the NLF was merely a puppet of Hanoi. Based on over a hundred interviews with former Communist cadre and high ranking Party officials as well as extensive archival research in Viet Nam, Robert K. Brigham's is a definitive work that provides a focus on the NLF not found elsewhere. It contributes greatly to our understanding of the Viet Nam War and encourages a reassessment of that conflict. Brigham assesses the impact of the NLF's diplomatic strategy on the conduct and outcome of hostilities, explores the origin and pursuit of its policy objectives, and defines its true relationship with North Viet Nam. He contends that the NLF's success in convincing the world that it was independent of Hanoi was critical in upsetting the political and military balance in South Viet Nam and frustrating the U.S. war effort. In addition, he argues that differences in goals among Communists-building socialism in the north, liberating the south-resulted in disagreements over responses to American intervention, and he shows how these differences entered into foreign relations and seriously undermined revolutionary efforts.